Luminous Daze in Paris - Jensen, Dorothy (LiNQ (Literature in North Queensland), 2016)
Dorothy Jensen reviews: Paris Studio, edited by Victor Barker and illustrated by Fred Cress. Halstead Press, 19a Boundary Street, Rushcutters Bay NSW 2011, 2001. ISBN 1 875684 78 6